ЛАБОРАТОРНАЯ МЕДИЦИНА — ФУНДАМЕНТ СОВРЕМЕННОЙ ТЕРАПЕВТИЧЕСКОЙ КЛИНИКИ - Л. П. Ефимова (Архивъ внутренней медицины, 2014)
Analytical reliability and clinical significance of laboratory data allows to consider them as a basis for diagnosis and treatment monitoring in therapeutic clinic. Laboratory biomarkers and predictors of use for risk assessment in clinical practice and disease prevention. Pre- and postanalytical stages of laboratory studies a large proportion of errors related to the actions of clinicians. Clinical laboratory diagnostics as a branch of medical science and the element of the health care system evolves, and this requires constant updating of knowledge in the discipline.